Do Mito da Natureza à Paródia da Verdolatria. Arquitectura Esverdeada - Duarte Jorge Ferreira Barroso Martins Pacheco (2012)
In the last few decades many attempts to conceptualize Nature have been made,in an effort to face our social and ecological condition. Trying to establish a sensefor the concept, many different disciplines have been agreeing with some fonnytheories, ending in interventions in the name of the environment, but whichpursuit only the profit, the ilusion of social salvation, or the fantasy to reach,through new techniques and technologies, a sustainable Nature, which, in itssupposed foundational principles, is only awaiting our salvation. That whichseems to be Un Inconvenient Truth reveals itself as a lie, often convenient forthose who seek in a false interpretation of the concept the reason to dictatepolitics and measures which, in general, if they are to be profiting, it is only forthose who apply them, inducing society into a polarized situation and into falseideas of sustainability, those of which seem to assure by themselves that theenvironmental issue is taken serious, and those of which avoid us to ask the vitaland sensitive question about the kind of solutions we really wish to achieve, andthe best way to achieve them.As a consequence, in a simplistic but ideologically powerfull way, the concept ofGreen has become to represent sustainability, becoming its incarnation in theModern World. Buildings fullfilled with technology, solar panels, self-timers orsimply vegetation or recicled materials, so called natural ones, have been invadingthe architectonic field, backed up by concepts which are exogenous to thediscipline's field of knowledge, becoming the problem to the very same solutionthey claim (but apparently do not intend) to be. But the Green also hides aperverse dimension... everything appears to be calm and harmonious but there issomething disturbing... rotting... The Green is the common lie, the secretconsensus, the perfect crime; everybody knows that it cannot be that good, that itcannot be that easy, but why bother? It sells, and there is enough Green foreverybody. In this work, we'll explore the expressions of this Green Architecture,perpetrating its origins, motivations and consequences, in such a way that we canunderstand what legitimacy can we really, if there is any whatsoever, give it. Wewill do such without renouncing to the critic attitude which understands theMan/Nature relation as unseparable, heterogeneous and unpredictable, andtherefore, above all, a complex political and social moment.